Феномен безобразного: от историко-культурологических истоков до социокультурных реалий наших дней - Фёдоров, Ю.В. (Культура народов Причерноморья, 2013)
У статті дається ретроспективний аналіз естетичної категорії «потворного» і конкретні
форми його присутності в сучасній культурі (мистецтві). Дана естетична категорія сьгодня набула
статусу культурологічного феномену та чітко вписана в соціокультурну реальність XXI століття. У
цій статті вона розглядається В статье дается ретроспективный анализ эстетической категории «безобразного» и
конкретные формы его присутствия в современной культуре (искусстве). Данная эстетическая
категория в настоящее время приобрела статус культурологического феномена и отчетливо вписана в
социокультурную реальность XXI столетия. В настоящей статье она рассматривается в контексте
глобального аксио-антропологического и культурного кризиса современной техногенной цивилизации. This paper provides a retrospective analysis of the aesthetic category of "ugliness" and the specific
forms of presence in contemporary culture (art). This aesthetic category has now acquired the status of cultural
phenomenon and clearly inscribed in the socio-cultural reality of XXI century. In this paper, it is considered in
the context of the global axiom of anthropological and cultural crisis of modern industrial civilization.
Ugliness as a phenomenon of artistic and aesthetic consciousness , abundantly fed Nietzschean, Bergson,
Freudian ideas in an atmosphere of frenzied race of scientific and technological achievements, it took a
significant place in the culture and art of XX-XXI century.The youth of today to look for at least some grain of beauty in the ugly is to recognize light, a hopeless, cultivate
healthy shoots in desperately sick, and this situation applies to virtually all types of forms and genres of
contemporary art. The media of "implantin” youth on anti-artistic and frankly pathological samples pseudo -
art (after all, the ugly, and appealing at the same time). In turn they go skillful manipulation of meanings, the
substitution of art concepts, destructive philosophies and questionable axiological category.
Art critics every day more and more difficult to understand the jumble of archaic images lurking in the depths of
the unconscious patients the authors skillfully powdered youth enticing lures and techniques of the super -
modern drive. Help them to therapists, psychologists, sexologists , philosophers, cultural. Here we must turn to
the modern system of interdisciplinary scientific synthesis of XXI century.